For kin or country xenophobia, nationalism, and war - Saideman, Stephen M. (Columbia University Press, 2008)
In addition to economic and political instabilities, the collapse of an empire can result in the division of families and the redrawing of geographical boundaries. This book considers various explanations for the causes of irredentism or for more restrained policy and the legacies of failed irredentist efforts.